Raw occurence data - Scherrer, Daniel; Christe, Philippe; Guisan, Antoine (Dryad Digital Repository, 2019)
This file contains the data from both the acoustic sampling and capture of bats with additional information about locations, field experts and bio-metric data of the bats.